Efficacy of Monocrotophos Against Ailanthus Webworm, Atteva fabriciella Swed. (Lepidoptera: Yponomeutidae) - Meshram, P. B., Jamaluddin (Indian Forester, 1989)
Four concentrations viz. (0.005%,0.01%, 0.0125% and 0.02%) of monocrotophos (36 E.C.) were tested as contact and systemic action against the larvae of Atteva fabriciella in field and laboratory conditions at room temperature. On the basis of experimental findings 0.02% monocrotophos exhibited 80 and 100 per cent mortality within 24 and 48 hours in field condition. The same treated leaves from field when fed to third ins tar larvae in the laboratory condition gave 80 and 100 per cent mortality after 24 and 48 hours respectively. The leaves directly treated in the same conditions at room temperature also gave 100 per cent mortality after 72 hours. Atteva fabriciella may be successfully controlled by applying 0.02% monocrotophos. (36 E.C.) in the nurseries and growing plantations of Ailanthus excelsa.